Challenges and the prospects of wheat (Triticum aestivum) improvement for limited irrigation in diverse production environments - MOHAN, DEVINDER; KHAN, HANIF; CHHOKAR, RAJENDER SINGH; TIWARI, RATAN; GUPTA, ARUN; JHA, ANKITA; SINGH, RANDHIR; SINGH, GYANENDRA (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted at ICAR-Indian Institute of Wheat and Barley Research, Karnal, Haryana in which performance of wheat (Triticum aestivum L.) varieties recommended for limited irrigation was compared utilizing the data generated in coordinated trials conducted during the period 2018–19 to 2022–23 at fixed sites in four agro- climatic zones of India. The yield loss, yield fluctuations, yield sustainability, shift in grain quality, physiological expressions and the key contributing traits were compared for the wheat varieties specific to such environments. In Indo-Gangetic plains (IGP), characterized as ME-1 by CIMMYT that includes two zones of northern India i.e. north- western plains zone (NWPZ) and north-eastern plains zone (NEPZ), limited irrigation expressed no abiotic stress on plant height, days to heading, maturity duration and grain weight and only grain bearing was adversely affected. In the warmer central-peninsular India (CPI) i.e. central zone (CZ) and peninsular zone (PZ) which is included in ME-5, there was a significant reduction in all the five traits. Yield reduction was highly significant in each zone and the yield loss varied zone-wise from 16% in NWPZ to 38% in PZ. It was more difficult to sustain wheat productivity under such situations. Protein content declined in IGP but CPI registered a significant gain in protein and gluten strength. Location specificity was apparent in each zone and durum was unsuitable for deficit irrigation. Farmer’s preference was restricted only to two zones namely CZ and NWPZ. For improving wheat varietal prospects under high temperature, supplementary irrigation has to be ensured at the time of heading beside CRI (crown root initiation) stage. This study suggested that irrigated wheat varieties can be tried for limited irrigation. The varieties that are particularly bred to tolerate moisture deficits should be preferred as the key yield contributing traits differ.